Role of neutrophils in different stages of atherosclerosis - Xiaojing Zhang; Zhanfang Kang; Dazhong Yin; Jun Gao (Innate Immunity, 2023)
Neutrophils constitute the first line of defense in human immunity and can be attracted to inflamed and infected sites by various chemokines. As essential players in immune processes, neutrophils theoretically play integral roles in the course of chronic inflammation-induced atherosclerosis. However, because neutrophils are rarely found in atherosclerotic lesions, their involvement in the pathophysiological progression of atherosclerosis has been largely underestimated or ignored. Recent research has revealed convincing evidence showing the presence of neutrophils in atherosclerotic lesions and has revealed neutrophil contributions to different atherosclerosis stages in mice and humans. This review describes the underlying mechanisms of neutrophils in different stages of atherosclerosis and highlights potential neutrophil-targeted therapeutic strategies relevant to atherosclerosis. An in-depth understanding of neutrophils’ roles in atherosclerosis pathology will promote exploration of new methods for the prevention and treatment of atherogenesis and atherothrombosis.